Avaliação do curso de Direito da UFT na perspectiva do egresso - Melo, Francisco Barbosa dos Santos (2019)
The 206th article of the Federal Constitution of Brazil presents many principles which conduct the public education in Brazil such as equalty of conditions in order to remain in school, liberty to learn, free education in public institutions, democratic administration of education intending to assure the right of good education to the population. To secure and control the quality of higher education was created in 1993 the National Program of Institutional Evaluation of Brazilian Universities (Programa de Avaliação Institucional das Universidades Brasileiras), in 1995 the National Exam of Courses (Exame Nacional de Curso) and in 2004 the National Evaluation System of Higher Edcucation (Sistema Nacional de Avaliação da Educação Superior – SINAES), in order to improve the quality of college education courses of institutions. Comprehending that encouraging the supply of higher education courses contributes to increase the number of graduated people which are accredited to operate in society, it we sought to know from this work the perception of former students who graduated in the period from 2010 to 2016 about the Law Course of Federal University of Tocantins (Universidade Federal do Tocantins – UFT). The method in the research is deductive, of quantitative and qualitative nature, it was possible to present data that contributed to evalute the Law Course of UFT. The data was collected from the application of a quiz containing four dimentions which were guided to supply the evaluation of the course. 421 e-mails were sent containing a quiz with 34 itens about the perception of graduated former students concerning professional performance, quality of teaching of the course, the infrastructure of the course and UFT itself and the college relationship with former students who graduated. The quiz contained a space so the former student could openly write about his experience during the course and to analyze these data, being applied Bardin’s qualitative technique of content analysis. Of the 421 quizes which were sent, 274 were properly answered. Concerning items of professional performance dimentions it was realized that about 89% of former students are employed, 60,2% work and live in the State of Tocantins and 37,6% receive between five and ten minimum wage, on average 31% are satisfied with the quality of the course. The data also showed that in general the course was well evaluated, with 72% of the answers between "good" and "great". All items related to the infrastructure of the university need to be improved according to graduated students’ conclusions about the course, which leads to other researchers developed with graduated former students of another higher education institutions.